Study of Thermal Effects in Fused-Tapered Pure Passive Fibers and Signal Combiners - Yuyi Yin; Tingwu Ge; Guanrui Zhao; Ruoyu Jia; Zhiyong Wang (Nanomaterials)
This paper investigates the thermal effects in fused-tapered passive optical fibers under near-infrared absorption. The thermal effect is primarily caused by impurities, such as OH-, which absorb incident light and generate heat. Using the finite element method, the volume changes during fiber tapering were simulated, influencing power density and thermal distribution. The heat conduction equation and ray optics were employed to analyze the thermal distribution in tapered fibers and signal combiners. Results show that at 5 kW power, the temperature peak for a single fiber reaches 316.73 °C, while for bundled fibers, the temperature rises significantly as the bundle configuration increases from 7 × 1 to 61 × 1, peaking at 453.09 °C—an increase of 171.6%. Variations in tapering ratio and length also notably affect the thermal behavior. Increasing the tapering ratio from 5 to 8 results in a 52.5% temperature rise, while doubling the taper length from 25 mm to 50 mm reduces the temperature peak by 59.1%. These findings offer important insights for the design and optimization of high-power optical fiber combiners and their heat dissipation structures.